High spin states of 195Hg - Fotiades Ν.; Harissopulos, S.; Kalfas, C. A.; Kossionides, S.; Serris, M.; Papadopoulos, C. T.; Vlastou, R.; Fallon, P.; Mullins, S. M.; Rilley, M. A.; Sharpey-Schaffer, J. F. (HNPS Advances in Nuclear Physics, 2019)
High spin states in 195Hg, populated using the 150Nd(48 Ca,3n) reaction, were investigated by γ-ray spectroscopic techniques. Two backbendings are observed in the yrast band considered to be caused by the alignment of a pair of i13/2 and p3/2 neutrons respectively. The strong backbending behaviour observed in the negative parity side band is consistent with the alignment of a pair of i13/2 neutrons. The similarity with the corresponding backbendings in the neighbouring isotopes is impressive.